2016
DOI: 10.1186/s13068-016-0660-5
|View full text |Cite
|
Sign up to set email alerts
|

Flowthrough pretreatment with very dilute acid provides insights into high lignin contribution to biomass recalcitrance

Abstract: BackgroundFlowthrough pretreatment is capable of removing much higher quantities of hemicellulose and lignin from lignocellulosic biomass than batch pretreatment performed at otherwise similar conditions. Comparison of these two pretreatment configurations for sugar yields and lignin removal can provide insights into lignocellulosic biomass deconstruction. Therefore, we applied liquid hot water (LHW) and extremely dilute acid (EDA, 0.05%) flowthrough and batch pretreatments of poplar at two temperatures and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…The Accellerase® 1500 cellulase enzyme cocktail was kindly provided by DuPont Industrial Biosciences (Palo Alto, CA). The BCA protein content of Accellerase® 1500, as reported elsewhere, 72 was 82 mg mL −1 . C. thermocellum DSM 1313 wild type was kindly provided by Prof. Lee Lynd at Dartmouth College, Hanover NH.…”
Section: Discussionmentioning
confidence: 99%
“…The Accellerase® 1500 cellulase enzyme cocktail was kindly provided by DuPont Industrial Biosciences (Palo Alto, CA). The BCA protein content of Accellerase® 1500, as reported elsewhere, 72 was 82 mg mL −1 . C. thermocellum DSM 1313 wild type was kindly provided by Prof. Lee Lynd at Dartmouth College, Hanover NH.…”
Section: Discussionmentioning
confidence: 99%
“…28 Similarly, the flowthrough dilute acid pretreatment is also capable of removing substantial amounts of lignin from lignocellulosic biomass, indeed more lignin could be solubilized in a flowthrough pretreatment than in a batch pretreatment performed under similar conditions. 29 For example, nearly 36% of lignin was removed from poplar in a flowthrough dilute acid pretreatment at 180°C while the lignin content in the batch pretreated poplar remained at the same level compared to that in the untreated sample. 29 On the other hand, the majority of the literature results reported that the percentage of K-lignin content of acid-pretreated biomass to be much higher than that of the untreated material as shown in Table 1.…”
Section: Pseudo-lignin Formation During Biomass Pretreatment Processesmentioning
confidence: 99%
“…29 For example, nearly 36% of lignin was removed from poplar in a flowthrough dilute acid pretreatment at 180°C while the lignin content in the batch pretreated poplar remained at the same level compared to that in the untreated sample. 29 On the other hand, the majority of the literature results reported that the percentage of K-lignin content of acid-pretreated biomass to be much higher than that of the untreated material as shown in Table 1. This phenomenon has been reported for hardwood, softwood, and herbaceous energy crops.…”
Section: Pseudo-lignin Formation During Biomass Pretreatment Processesmentioning
confidence: 99%
“…However, the employment of mineral acids has some disadvantages, such as the expensive catalyst recovery and the possible corrosion of the stainless steel equipment. About the last issue, it is reported that the use of H 2 SO 4 concentration higher than 0.05 wt% can rapidly corrode a Type 316 stainless steel (widely used for the construction of autoclaves), even at moderate temperature and time, typical of the hydrothermal pretreatments [36]. Therefore, common stainless steels cannot be adopted for the acid hydrothermal treatments, which instead require special alloys, such as various grades of Hastelloy, zirconium or other corrosion-resistant alloys, which ensure excellent corrosion resistance to acids, even at high severity conditions [37].…”
Section: Introductionmentioning
confidence: 99%